2015
DOI: 10.1371/journal.pone.0125042
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Discrimination Factors of Stable Carbon and Nitrogen Isotopes in Hair of Corn Fed Wild Boar

Abstract: Stable isotope measurements are increasingly being used to gain insights into the nutritional ecology of many wildlife species and their role in ecosystem structure and function. Such studies require estimations of trophic discrimination factors (i.e. differences in the isotopic ratio between the consumer and its diet). Although trophic discrimination factors are tissue- and species- specific, researchers often rely on generalized, and fixed trophic discrimination factors that have not been experimentally deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…[21][22][23][24] According to these studies, δ 13 C values for mammalian hair of −15 ‰ can be attributed to an almost completely corn-based diet. 21,22,24 On the other hand, δ 13 C values of −24 ‰ and lower are attributed to exclusively C 3 -plants in the diet. 21,22,24…”
Section: Sample Preparation Of Urine For Gc-c-irmsmentioning
confidence: 96%
See 4 more Smart Citations
“…[21][22][23][24] According to these studies, δ 13 C values for mammalian hair of −15 ‰ can be attributed to an almost completely corn-based diet. 21,22,24 On the other hand, δ 13 C values of −24 ‰ and lower are attributed to exclusively C 3 -plants in the diet. 21,22,24…”
Section: Sample Preparation Of Urine For Gc-c-irmsmentioning
confidence: 96%
“…7 The endogenous-like carbon isotopic signature of urinary NorA after consumption of "castrated pig edible parts" was reported in the past, although no δ 13 C values were presented proving the validity of this statement. 24 The bristles analyzed showed that several months before, the dietary source of the animal had been completely different, with δ 13 C values of −24 ‰ and thus without a major contribution of corn in the diet. This has been determined, for example, using hair [25][26][27][28][29][30] was shot mid-January 2018, thus plausibly matching the carbon isotopic signature of an animal that was completely fed on corn.…”
Section: δ 13 C Of Boar Bristlesmentioning
confidence: 99%
See 3 more Smart Citations